Electrophysiological and anatomical background of the fusion configuration of diastolic and presystolic Purkinje potentials in patients with verapamil‐sensitive idiopathic left ventricular tachycardia. Issue 5 (24th February 2015) - Taniguchi, Hiroshi; Kobayashi, Yoshinori; Maruyama, Mitsunori; Morita, Norishige; Hayashi, Meiso; Miyauchi, Yasushi; Shimizu, Wataru
Abstract: Background: It is unclear whether false tendons (FTs) are a substantial part of the reentry circuit of verapamil‐sensitive idiopathic left ventricular tachycardia (ILVT). This study aimed to prove the association between FTs and the slow conduction zone by evaluating the electro‐anatomical relationship between the so‐called diastolic Purkinje (Pd) potentials and FTs using an electro‐anatomical mapping (EAM) system (CARTO). Methods: The 1st protocol evaluated the spatial distribution of Pd and presystolic Purkinje (Pp) potentials in 6 IVLT patients using a conventional CARTO system. In the remaining 2 patients (2nd protocol), the electro‐anatomical relationship between the Pd–Pp fusion potential and the septal connection of the FT was evaluated using an EAM system incorporating an intra‐cardiac echo (CARTO‐Sound). Results: Pd potentials were observed in the posterior–posteroseptal region of the LV and had a slow conduction property, whereas Pp potentials were widely distributed in the interventricular (IV) septum. At the intersection of the 2 regions, which was located in the mid‐posteroseptal area, both Pd and Pp potentials were closely spaced and often had a fused configuration. In the latter 2 patients (2nd protocol), it was confirmed that the intra‐cardiac points at which the Pd–Pp fusion potential was recorded were located in the vicinity of the attachment site of the FT to the IV septum. In all patients, ILVTs were successfully eliminated by the application of radiofrequency at those points. Conclusion: FTs may at least partly contribute to the formation of the Pd potential, and thus form a critical part of the reentry circuit of ILVT.